Paramedics’ knowledge of the symptoms and prehospital care of patients with Prader-Willi and Angelman syndromes - Jóżwicki, Kamil; Maniukiewicz, Berenika; Rajter, Beata; Jarzynka, Sylwia (Medical Studies/Studia Medyczne, 2025)
Introduction: Rare genetic disorders are conditions in which the emergency medical team’s knowledge of characteristic clinical and phenotypic symptoms can significantly improve the quality of the provided medical care. Aim of the research: This study focuses on assessing paramedics’ knowledge of characteristic symptoms that may influence the emergency procedures in patients with rare Prader-Willi and Angelman genetic syndromes. This topic was chosen due to the lack of guidelines for emergency care of patients with genetic disorders, posing a major challenge in medical practice. Material and methods: The survey was conducted among 100 paramedics. The research took place at the Medical University of Warsaw in Poland. An author`s survey questionnaire consisting of closed-ended single-choice and multiple-choice questions was used. Statistical analyses were performed using descriptive statistics and correlation analysis. Results: Paramedics’ overall knowledge of Prader-Willi and Angelman syndromes and related emergency procedures was low (around the 50th percentile in knowledge score statistics), and the results indicated a statistically significant deviation from the normal distribution (Shapiro-Wilk test, p < 0.001). Individuals of varying ages, work experience, workplace settings, educational backgrounds, and genders did not differ in their knowledge of the symptoms and emergency procedures related to these selected genetic disorders (Spearman’s rank correlation, Mann-Whitney U test, Kruskal-Wallis test). The rising prevalence of genetic disorders highlights the growing need to address this issue in training and practice. Conclusions: There is a need for education and continuous professional training for paramedics regarding general knowledge and emergency medical procedures for individuals with Prader-Willi syndrome and Angelman syndrome as rare genetic disorders.